Provision of mouth-care in long-term care facilities: an educational trial - MacEntee MI, Wyatt CCL, Beattie BL, Paterson B, Levy-Milne R, McCandless L, (Blackwell Synergy, 2007)
This randomized clinical trial aimed to assess the effectiveness of a pyramid-based education for improving the oral health of elders in long-term care (LTC) facilities